A avaliação do estudante em atividades de Modelagem Matemática: o que as pesquisas apontam? - Pinto, Amanda Ribeiro (2018)
The use of Modeling in Mathematics classes has been advocated for decades by the community of researchers in Modeling in Mathematics Education. Several scholars and teachers have been dedicated to researching the challenges, possibilities and contributions that involve this practice. However, there are few proposals and discussions about student evaluation in this context. Based on the assumption that there is a Brazilian production of research aimed at investigating the practice of Modeling based on classroom activities, especially in Basic Education, the present research proposes to answer the following question: what Brazilian researches indicate the student's assessment of Mathematical Modeling activities developed in Basic Education? To answer this question, we intend to identify and analyze in the dissertations and theses that developed Mathematical Modeling activities in Basic Education the expressions about the student's assessment in this context. Considering the question and the objective to be achieved, we take a qualitative approach to this research, which is also characterized as a documentary study. We selected 73 papers that met our objective, which were defended from 2006 to 2016. For the organization, data construction and definition of categories, the Content Analysis procedures were used. The four categories that emerged from this process were: 1) Criteria for assessment and Mathematical Modeling; 2) Tools for assessment and Mathematical Modeling; 3) Evaluative Practices and Mathematical Modeling and 4) Consequences of the evaluative practices under the activities of Mathematical Modeling. The analysis points out that although the evaluative practices identified in the dissertations and theses have sought agreement with the proposals of some modeling models in Mathematics Education, considering the elements that constitute it, it is perceived that these are guided by traditional evaluative practices present in the scope school.